(untitled) (Clinics, 2022)
Purpose: To determine the clinical and anatomical characteristics associated with obstructive sleep apnea severity in children with adenotonsillar hypertrophy. Methods: The authors conducted a cross-sectional multidisciplinary survey and selected 58 Brazilian children (4‒9 years old) with adenotonsillar hypertrophy, parental complaints of snoring, mouth-breathing, and witnessed apnea episodes. The authors excluded children with known genetic, craniofacial, neurological, or psychiatric conditions. Children with a parafunctional habit or early dental loss and those receiving orthodontic treatment were not selected. All children underwent polysomnography, and three were excluded because they showed an apnea-hypopnea index lower than one or minimal oxygen saturation higher than 92%. The sample consisted of 55 children classified into mild (33 children) and moderate/severe (22 children) obstructive sleep apnea groups. Detailed clinical and anatomical evaluations were performed, and anthropometric, otorhinolaryngological, and orthodontic variables were analyzed. Sleep disorder symptoms were assessed using the Sleep Disturbance Scale for Children questionnaire. All children also underwent teleradiography exams and Rickett's and Jarabak's cephalometric analyses. Results: The mild and moderate/severe obstructive sleep apnea groups showed no significant differences in clinical criteria. Facial depth angle, based on Ricketts cephalometric analysis, was significantly different between the groups (p = 0.010), but this measurement by itself does not express the child's growth pattern, as it is established by the arithmetic mean of the differences between the obtained angles and the normal values of five cephalometric measurements. Conclusions: The clinical criteria and craniofacial characteristics evaluated did not influence the disease severity.